Ten Facts on Declining Business Dynamism and Lessons from Endogenous Growth Theory - Ufuk Akcigit; Sina T. Ates (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this paper, we review the literature on declining business dynamism and its implications in the United States and propose a unifying theory to analyze the symptoms and the potential causes of this decline. We first highlight 10 pronounced stylized facts related to declining business dynamism documented in the literature and discuss some of the existing attempts to explain them. We then describe a theoretical framework of endogenous markups, innovation, and competition that can potentially speak to all of these facts jointly. We next explore some theoretical predictions of this framework, which are shaped by two interacting forces: a composition effect that determines the market concentration and an incentive effect that determines how firms respond to a given concentration in the economy. The results highlight that a decline in knowledge diffusion between frontier and laggard firms could be a significant driver of empirical trends observed in the data. This study emphasizes the potential of growth theory for the analysis of factors behind declining business dynamism and the need for further investigation in this direction.
Keywords: E22; K20; L10; L41; O33; O34; 330; business dynamism; market concentration; markups; competition; knowledge diffusion; innovation; patenting